Electromyographic analysis of locomotion for healthy and hemiparetic subjects—study of performance variability and rail effect on treadmill - Hwang, Ing-Shiou; Lee, Hsin-Min; Cherng, Rong-Ju; Chen, Jia-Jin J (Gait & posture, 2003)
This study quantified the performance variability and effect of rail support on the ankle joint for normal and hemiparetic subjects during treadmill walking. Muscle activities of the anterior tibialis (TA) and medial gastrocnemius (MG) from six hemiparetic patients and 14 healthy subjects were assessed with EMG linear envelope and variance ratio of consecutive strides at self-selected cadences. Our results indicate that (1) performance consistency of the hemiparetic patients was significantly undermined; (2) habituated process during treadmill walking was notable in the MG but not in the TA; and (3) rail support could reduce performance variability of the ankle antagonist pairs.